Categorizing 10 Sports According to Bone and Soft Tissue Profiles in Adolescents. Issue 12 (December 2020) - AGOSTINETE, RICARDO RIBEIRO; FERNANDES, ROMULO ARAÚJO; NARCISO, PEDRO HENRIQUE; MAILLANE-VANEGAS, SANTIAGO; WERNECK, ANDRÉ OLIVEIRA; VLACHOPOULOS, DIMITRIS
ABSTRACT: Purpose: Considering the different loading and training characteristics of the sports practiced during growth, it is important to specify and categorize the bone and soft tissue adaptations in adolescent athletes. This study aimed to categorize 10 different loading sports and a nonsport group and identify the differences in bone density and soft tissues. Methods: The sample included 625 adolescents (10 to 17 yr of age) of 10 sports (soccer, basketball, volleyball, track and field, judo, karate, kung fu, gymnastics, baseball, and swimming) and a nonsport group. Dual-energy x-ray absorptiometry assessed areal bone mineral density (aBMD), bone mineral apparent density (BMAD), and soft tissues (lean soft tissue and fat mass). The results were adjusted for sex, peak height velocity status, lean soft tissue, fat mass, and weekly training volume. Results: The comparisons among groups showed that soccer had the highest whole-body aBMD (mean ± SEM: 1.082 ± 0.007 g·cm −2 ) and lower limb aBMD (1.302 ± 0.010 g·cm −2 ). Gymnastics presented the highest upper limb aBMD (0.868 ± 0.012 g·cm −2 ) and whole-body BMAD (0.094 ± 0.001 g·cm −3 ). Swimming presented the lowest aBMD values in all skeletal sites (except at the upper limbs) and whole-body BMAD. The soft tissue comparisons showed that soccer players had the highest lean soft tissue (43.8 ± 0.7 kg). The lowest fat mass was found in gymnasts (8.04 ± 1.0 kg). Conclusion: The present study investigated and categorized for the first time 10 different sports according to bone density and soft tissue profiles. Soccer and gymnastics sport groups were found to have the highest bone density in most body segments, and both sports were among the groups with the lowest fat mass.